Research on the Formation Mechanism of Health Insurance Fraud in China: From the Perspective of the Tripartite Evolutionary Game - Fei, Yun; Fu, Yi; Yang, Dong-xiao; Hu, Chang-hao (Frontiers in Public Health, 2022)
The problem of defraud reimbursement in China’s Health Insurance has existed for a long time and is becoming more serious, which needs to be solved urgently. This paper constructs a tripartite evolutionary game model, game participants including medical administrative organization (MAO, a government department responsible for Health insurance supervision), medical institution (MI, such as hospital) and insured individuals (II, who participating in medical and healthcare insurance). By analyzing the equilibrium results of the tripartite evolutionary game, this paper makes an in-depth study on the formation and resolution of the above problems. The results show that: (1) How to stop the fraud behavior of medical institutions is the difficulty and core of the problem. To solve this problem, it is necessary to achieve the effective supervision of medical administrative organization, the internal management of medical institutions and the social supervision of insured individuals. (2) The regulatory behavior of the MAO needs to focus on protecting the interests of insured individuals, not only to encourage the insured individuals to actively play the role of supervision and reporting, but also to prevent their collusion with medical institutions. (3) On the one hand, the MAO need to strengthen supervision and increase the punishment for fraud. On the other hand, they also need to take incentive measures to guide all subjects to form a sound internal management mechanism.